Use of endoscopic ultrasound‐guided fine needle aspiration of the pancreas to diagnose a case of primary linitis plastica of the colon with retroperitoneal dissemination. Issue 1 (5th July 2021) - Shitani, Masahiro; Ogino, Jiro; Akahonai, Masakazu; Isosaka, Mai; Ota, Shigenori; Tayama, Yoshiko; Ueki, Tomomi; Tsuruma, Tetsuhiro; Adachi, Takeya; Hirata, Koichi; Nakase, Hiroshi
ABSTRACT: A 54‐year‐old man had previously undergone curative sigmoidectomy for poorly differentiated adenocarcinoma with a signet‐ring cell component of the sigmoid colon, which was characterized morphologically by stenosis and inelasticity of the colon (linitis plastica). Six weeks after surgery, the patient developed stenosis of the right ureter. Disseminated sigmoid cancer was suspected, and chemotherapy was started. Nine months after initiation of chemotherapy, obstructive jaundice was observed which was due to stenosis of the distal bile duct (BD). Although computed tomography showed no evident metastatic lesion that could cause the stenosis, swelling of the entire pancreas was evident compared to that of 11 months earlier. Endoscopic ultrasound (EUS) also did not detect any focal masses in the head of the pancreas, although there was a diffuse hypoechoic change in the entire pancreas. Histopathology of the stenotic BD and biopsy specimen from the head of the pancreas showed no malignant cells. Two months after the initial endoscopic bile duct drainage, the patient was admitted again for epigastric pain. A second EUS fine needle aspiration (EUS‐FNA) of the head of the pancreas was performed and showed poorly differentiated carcinoma with some signet‐ring cells. This finding provided histological confirmation of a disseminated pancreatic lesion of the previously resected linitis plastica of the sigmoid colon. This is a rare case of disseminated pancreatic lesion from primary linitis plastica of the colon diagnosed by EUS‐FNA.